MODEL ON NATURAL SCIENCES SUBJECT (IPA) GRADE IV ELEMENTARY SCHOOL - Widiastuti, Shendi Kharisma (International Journal of Elementary Education, 2017)
This study aimed to produce a product namely learning media in the form of flashcardon the theme of "Tempat Tinggalku" for elementary school students grade IV which suit for use and in accordance with the needs of students and to improve student learning outcomes. This type of research was research development (research and development). The initial product that has been created through the validation process is done by the learning media experts and subject matter experts. Furthermore, this product was tested to students through two stages namely, limited trials and extensive trials. The limited trial subjects consisted of 10 fourth graders of elementary school, and 36 students in extensive trials. Other data collected in this study was the response of teachers, students’ response and students’ learning outcomes after using flashcard media. The average result of students' written test on pretest was 51.86 while the post test was 87.28. This proves that there is significant increase of learning outcomes that was equal to 35,42. These results come from written tests before students used the media and after using the learning media. The average result of student learning outcomes increased after they participated in the learning activity by using flashcard media.